Heidelberger Interprofessionelle Ausbildungsstation (HIPSTA): a practice- and theory-guided approach to development and implementation of Germany’s first interprofessional training ward - Mihaljevic, André L. (GMS J Med Educ, 2018)
Background: Deficits in care and impaired patient-safety have been linked to inefficient interprofessional collaborative practice. Interprofessional training wards (IPTW) are an interprofessional educational intervention which aim to enable students and trainees from different health professions to work self-responsibly in order to manage the medical treatment and rehabilitation of real-life patients together as an interprofessional team. We aimed to develop and implement Germany´s first IPTW at the department of Surgery at Heidelberg University Hospital. Methods: The Kern cycle was used to develop an ITPW curriculum. Practical as well as theoretical considerations guided the design of the IPTW. Common project management tools including blueprinting and RASCI (Responsibility, Approval, Support, Consultation, Information) matrix were applied. Results: Since April 2017, 7 cohorts of students and trainees have had four-week long placements on HIPSTA. They run the IPTW in early and late shifts. Nursing and medical facilitators are supporting the IP team as needed. Learning objectives are operationalized as EPAs (entrustable professional activities) and interprofessional learning goals. Since initiation only minor modifications to the curriculum have been necessary and satisfaction of students/trainees, facilitators and patients is high. Conclusion: IPTWs can be established and run in the German health care system even in a complex clinical setting. The early involvement of all professions in a steering group seems to be key to success. Nursing and medical facilitators are of utmost importance for daily routine. The experiences outlined here could help others aiming to implement IPTWs at their sites. IPTWs might address a number of hitherto unaddressed educational needs. Trial registration: Not applicable